LAST NIGHT I DREAMED OF PEACE: AN EXTRAORDINARY DIARY OF COURAGE FROM THE VIETNAM WAR - Rakumakoe, Lesedi Dawn (Scientia Militaria - South African Journal of Military Studies, 2014)
Many people’s view about war and its impact was changed by a woman named Dang Thuy Tram. Her diaries, which she kept as a practicing medical doctor during the Vietnam War, were published some forty odd years after her death. The diaries contain personal accounts of how she viewed and experienced the Vietnam War. The publication of the diaries made headlines in the non-English reading world.